On the love of obedience: comments on the freedom and irrationality of law - Lombardi Daibem, Ana Maria [UNESP]; Costa, Matheus Bento (Univ Federal Fluminense, Inst Ciencias Humanas & Filosofia, 2020)
The ability to choose based on the perception of logical reasoning is the very foundation of justice as a modern normative system. It is what renders the individual responsible for their actions, allowing them to be classified as a criminal when in breach of the law. It is also this ideal of freedom that locates law and justice as products of human will in the Western tradition. The following article questions this tradition by harnessing its intersections with politics and philosophy in order to problematize the issue of what is just and what is unjust by means of the view that obedience, although it may be chosen, is not necessarily rational.
Keywords: Justice; reason; freedom; obedience; love